2021
DOI: 10.14429/dsj.71.16468
|View full text |Cite
|
Sign up to set email alerts
|

Active Flow Control over a NACA23012 Airfoil using Hybrid Jet

Abstract: A time-dependent numerical simulation is performed to examine the flow separation control with the action of a hybrid jet (the combination of synthetic and continuous jets) over a NACA23012 airfoil. The unsteady Reynolds-averaged Navier–Stokes (URANS) simulation is performed with Spalart-Allmaras (SA) turbulence model to simulate the flow field around the airfoil to analyse the effect of the hybrid jet. A combined jet is placed at the point of flow separation on the upper surface of the airfoil which is locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…In terms of aerodynamic improvement, the unsteady jet devices can perform equally well or, in some cases, present superior control performance when compared to the steady jet, with the advantage of requiring a reduced mass blowing rate from the system. Recent studies, which also combine continuous and oscillatory jets as carried out by Seifert et al (1993), were performed by Singh et al (2021). Instead of supplying the hybrid jet to the flap region, the research was based on the jet application to the leading edge (12% c), where a significant stall delay was observed, changing the angle of stall from 16° to 20° when the mean velocity of the hybrid jet was equal to the free stream.…”
Section: Active Flow Controlmentioning
confidence: 99%
“…In terms of aerodynamic improvement, the unsteady jet devices can perform equally well or, in some cases, present superior control performance when compared to the steady jet, with the advantage of requiring a reduced mass blowing rate from the system. Recent studies, which also combine continuous and oscillatory jets as carried out by Seifert et al (1993), were performed by Singh et al (2021). Instead of supplying the hybrid jet to the flap region, the research was based on the jet application to the leading edge (12% c), where a significant stall delay was observed, changing the angle of stall from 16° to 20° when the mean velocity of the hybrid jet was equal to the free stream.…”
Section: Active Flow Controlmentioning
confidence: 99%
“…The study revealed that the synthetic jet is an effective method of removing hot spots in many engineering and industrial applications, i.e., processors and electronic chips. Other engineering applications of hybrid jet (combinations of synthetic and continuous jet) is also discussed in Singh et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among various active flow control techniques, the synthetic jet presents a novel and innovative approach due to some of its features. Simple evaluation studies of synthetic jets without any application in jet engines have been reported by Smith and Glezer [33], Seifert and Pack [34], McCormick [35], Glezer and Amitay [36], Rediniotis et al [37], Smith and Swift [38], Mathis et al [39][40], You and Moin [41], Aram and Mittal 42-43], Mohseni and Mittal [44], Singh et al [45]. The synthetic jet was used for a plethora of applications by the researchers, namely, Smith and Glezer [33] for thrust vectoring, Utturkar et al [46][47], Gallas et al [48] for heat transfer enhancement, Zhang et al [49], Kim and Kim [50], and Lin et al [51] for turbomachinery, and Yadav et al [52][53] for flow control in air-intake ducts.…”
Section: Introductionmentioning
confidence: 99%